ANÃLISE DA ATIVIDADE HORMONAL DE TIAMETOXAM ATRAVÉS DE BIOTESTES - Castro, Paulo R. C.; Pitelli, Angélica M. C. M.; Peres, Lázaro E. P.; Aramaki, Paulo H. (REVISTA DE AGRICULTURA, 2015)
ANÃLISE DA ATIVIDADE HORMONAL DE TIAMETOXAM ATRAVÉS DE BIOTESTES